(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
The article examines the key role of emotional intelligence (EI) in the educational process. The focus is on the importance of developing EI in students, the impact of this process on academic and social success, and the methods and strategies that can be used to foster emotional development in the educational environment. The article also emphasises the role of educators and in supporting and developing students’ emotional intelligence. This material will be useful for both educational professionals and parents seeking to better understand and support their children’s emotional development.